Online particle size distribution estimation of a mixture of similar sized particles with acoustic emissions - Nsugbe, Ejay; Starr, Andrew; Jennions, Ian K.; Ruiz Carcel, Cristobal (IOP Publishing, 2017)
Particle processing plants regard the Particle Size Distribution (PSD) as a key quality factor as it influences the bulk and flow properties of the particles. In this work, Acoustic Emission (AE) is used to estimate the PSD of a mixture that comprise of similar sized particles. The experiments involved the use of regular sized particles (glass beads) and with the aid of a time domain based threshold analysis of the particle impacts the PSD of the mixtures could be estimated.